Entrepreneurship, innovation and sustainability - Wagner, Marcus, 1973- (Sheffield : Greenleaf Pub., 2012)
This book addresses the intersection of entrepreneurship, innovation and sustainability (EIS), presenting high-quality research illuminating the relationship between the three fields.
Section I. Integrative views of the EIS nexus -- section II. Corporate entrepreneurship for sustainability-improving innovation -- section III. EIS in mature industries -- section IV. EIS in developing countries -- section V. EIS in small firms -- section VI. EIS in a network perspective.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Entrepreneurship; Industrial management; Social responsibility of business; Sustainable development; Creative ability in business; Entrepreneuriat; Gestion d'entreprise.; Entreprises -- Responsabilité sociale; Développement durable; Créativité dans les affaires; entrepreneurs; sustainable development; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Creative ability in business; Entrepreneurship; Industrial management; Social responsibility of business; Sustainable development